Aplicação da norma IEC 61850 em automação de subestações de energia elétrica - SOUZA, Bruno Pereira de (2018)
This paper will present the international standard IEC 61850, identifying its general applicability to the existing automation in most industrial plants, explaining their characteristics and advantages in relation to increasing demand of modernization. Moreover, it will be explained how this standard operates in substations that allowing intelligent devices of different manufacturers can communicate without the use of protocol converters.